2012
DOI: 10.1039/c2ee22050d
|View full text |Cite
|
Sign up to set email alerts
|

Comb-shaped polymers to enhance hydroxide transport in anion exchange membranes

Abstract: Comb-shaped poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) polymers with quaternary ammonium (QA) groups have been synthesized organizing into well-defined micro-morphology for efficient anion (hydroxide) transport. These molecular comb structures show a dramatic enhancement in conductivity and water resistance compared with non-comb-shaped PPOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
241
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 340 publications
(254 citation statements)
references
References 39 publications
10
241
2
1
Order By: Relevance
“…As shown in Figure 14a, comb-shaped poly(2,6-dimethyl-1,4-phenylene oxide)s (PPO) with quaternary ammonium (QA) groups 30 and long alkyl side chains have been synthesized by bromination and amination reaction from inexpensive starting materials. 17,119 The unique polymer architecture results in nanophase separation between the conducting (quaternized PPO) and nonconducting domains (grafted alkyl chains) as confirmed by small-angle X-ray scattering (SAXS) ( Figure 14c) 119 and thus gives rise to high anion conductivities. An important characteristic is that the comb-shaped membranes exhibited a much lower water uptake (10−20 wt %) but a comparable conductivity compared with the values reported for many QA-AEMs in the hydroxide form.…”
Section: Anion Exchange Membranesmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 14a, comb-shaped poly(2,6-dimethyl-1,4-phenylene oxide)s (PPO) with quaternary ammonium (QA) groups 30 and long alkyl side chains have been synthesized by bromination and amination reaction from inexpensive starting materials. 17,119 The unique polymer architecture results in nanophase separation between the conducting (quaternized PPO) and nonconducting domains (grafted alkyl chains) as confirmed by small-angle X-ray scattering (SAXS) ( Figure 14c) 119 and thus gives rise to high anion conductivities. An important characteristic is that the comb-shaped membranes exhibited a much lower water uptake (10−20 wt %) but a comparable conductivity compared with the values reported for many QA-AEMs in the hydroxide form.…”
Section: Anion Exchange Membranesmentioning
confidence: 99%
“…A number of well-defined copolymer architectures having nanochannels for anionic transport (block, 16 graft copolymers 17,119 ) have been reported in the literature. For practical applications, an anionic conductivity of >50 mS cm at 80°C needs to be achieved.…”
Section: Outlook and Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Li et al showed that changing the cation from quaternary benzyl trimethylammonium (TMA + ) to quaternary benzyl N,N-F687 dimethylhexylammonium (DMH + ) on a PPO backbone mitigated the backbone hydrolysis degradation mode. 36,37 Additionally, crosslinking PPO with quaternary benzyl DMH + cations further enhanced AEM mechanical stability in alkaline solutions. 18 We found these results surprising given that we had shown that changing the electron donating character of cation group at the benzyl position on a PSF backbone did not influence cleavage of the polymer backbone.…”
mentioning
confidence: 99%